BUSANA PESTA SORE DENGAN LEKAPAN BORDIR KUPU-KUPU MORPHO BIRU - Risa Robiani Divani Achmad; Marlina Marlina (Fesyen Perspektif, 2017)
Blue Menealous Morpho is more than one butterfly with a sparkling wing sides and a large ocelli line at the base of the postdical area. This butterfly is a neotropical, found mostly in central America, Mexico and South Amerika, including, Brazil, Costa Rico and Venezuela. Blue morpho butterfly model became an inspiration to be used as a garniture in the evening party dress. Party dress is a special dress that is used for the occasion of the party and has special characteristics ranging from design to various kinds of garniture to complement a beautiful and luxurious impression on the party dress. Characteristics of morpho butterfly became an inspiration for the party dress garniture which is realized, using embroidery techniques, that added with a paste sequin decoration that will complement a luxurious impression on the party dress. This scientific work is prepared using experimental methods. The authors designed it to realize the party dress with a silhouette that is given with the technique embroidery morpho blue butterfly.